Editorial: Change Publication Frequency in 2019 - Iqbal, Muhammad Naeem; Ashraf, Asfa (PSM Biological Research, 2018)
Editorial: We are pleased to announce that starting in January 2019; PSM Biological Research will publish four quarterly online issues (November–January, February–April, May–July, and August–October). This change will facilitate expanded discoverability of the contents via a quarterly Table of Contents, indexing, and other archival services in a timely manner. The journal works on open access policy and provides immediate open access to all content in order to make research freely available to the public, and ensure a global exchange of knowledge. Articles are published online immediately after acceptance in the upcoming issues of the journal. PSM Biological Research is committed to publishing selective and high quality content that is accessible to researchers from a broad spectrum of disciplines. Topics include all aspects of life sciences and allied sciences, biological sciences, medical sciences, agricultural science, animal science, biotechnology, biochemistry, bioinformatics, genetics, molecular biology, environmental science, ecology, developmental biology, biodiversity and conservation, entomology, microbiology, immunology, neuroscience, marine biology, pharmacology and toxicology, pharmaceutical science, veterinary science, infectious diseases, public health, biomedical research, biomedical engineering, and more. Over the years, the valued contributions from the authors and the volunteer participation of the many dedicated colleagues in the peer-review process have been vital to the continuing strength and success of PSM Biological Research. We sincerely appreciate all your contributions and look forward to your continued enthusiasm and support in the coming years. Citation: Iqbal, M.N, Ashraf, A., 2018. Editorial: Change Publication Frequency in 2019. PSM Biol. Res., 3(3): 146-147.